Inflammatory and autoimmune diseases of the nervous system; possibilities of laboratory diagnostic methods in cerebrospinal fluid - Lodin, Z (Folia microbiologica, 2003)
Contemporary aspects of cerebrospinal fluid analysis are discussed, including the relationship to neuro-infective, autoimmune and other neurological diseases. The actual state of cerebrospinal fluid microbiological and cytological investigation and analysis of cerebrospinal fluid protein fractions are described in detail.
Keywords: mozkomíšní mok; Central Nervous System Diseases; nemoci centrálního nervového systému; lidé; autoimunitní nemoci nervového systému; Cerebrospinal Fluid; Humans; Autoimmune Diseases of the Nervous System